A Facile Approach for the Electrochemical Sensing of Dopamine using Paper-Based PEDOT:PSS/RGO Graphene Biosensor. (26th November 2020) - Settu, Kalpana; Huang, Yu-Ming; Zhou, Sheng-Xuan
Abstract : In this study, we have developed a paper-based electrochemical biosensor for dopamine (DA) detection. For this purpose, a screen-printed graphene electrode (SPGNE) was printed on a paper substrate, and the electrode surface was modified with PEDOT:PSS/RGO. The fabricated sensor was characterized by analyzing the capacitance, cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS) measurements. Differential pulse voltammetry (DPV) was employed for the quantitative detection of dopamine. The paper-based SPGNE biosensor developed in this study could detect dopamine in a linear range from 0.0125 to 0.1 mM with a sensitivity of 24.9 μ A mM −1 . The reliability of the developed biosensor for dopamine detection was assessed by using normal serum samples. The paper-based graphene biosensor proposed in this study could be low-cost and eco-friendly, and its ability to determine the dopamine from real serum samples showed promising results. The developed SPGNE dopamine-sensing biosensor could be potentially applied for the early-stage diagnosis of various neurological diseases/disorders.